Implementation of Village SDGs Program For Poverty Reduction in Sukorejo Village Bangsalsari District Jember Regency - Ach Ilyasi; Fitriatul Hasanah; Khusnul Khotimah; Kahar Haerah (Universitas Muhammadiyah Jember Press, 2026)
The implementation of the SDGs program at the village level in reducing poverty is crucial to improving the local economy and providing the necessary recommendations to achieve the 2030 sustainable development vision. The role of the village government is crucial in strengthening assistance programs aimed at reducing poverty while directly identifying supporting and inhibiting factors in the field. This study aims to research and analyze the implementation of the SDGs program at the village level in reducing poverty in Sukorejo Village, Bangsalsari District, Jember Regency. The method used is exploratory qualitative with a case study approach was used, including interviews, observations, and documentation. The results of the study indicate that the implementation of the SDGs program in Sukorejo Village has been carried out quite well, especially in poverty indicators, as reflected in the achievement of the SDGs, which has increased based on SID data from the Ministry of Villages. Thus, poverty levels, especially in Sukorejo Village, have decreased by 55.98%.